Lembaga Pendidikan Sains dan Teknologi pada Masa Islam Klasik - Nur Hamimah; Holida Munasti Pulungan; Kamil Gulo; Solihah Titin Sumanti; Yusnaili Budianti (Pascasarjana IAI Nasional Laa Roiba Bogor, 2024)
Islamic civilization had record as a gold in the trajectory of the world history due to the development of science and technology. The enthusiasm and motivation for knowledge from the Qur’an and Hadits as a source of inspiration for Moslems made the spirit driving the rise of Islamic civilization at that time, marked by the development of science and technology. In its development, of course the emergence of science and technology in the Islamic world cannot be separated from the science and technology institutions that make the biggest contribution. This paper tries to describe several educational institutions such as hospital libraries and observatories as institutions that contribute to the development of science and technology at that time. The existence of a library is not only a place to read its name as well as to study research and also to discuss science and technology as well as the existence of a hospital not only as a place for birds but also to be a place for medical science practice and no less important is the existence of an observatory for conducting research.